Parental assistance in nutrition management of stunting toddlers through home care nursing visits - Ari Setiawati; Rusli Rusli; Anita Lotaan (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2025)
Stunting remains a major public health problem in developing countries, particularly among toddlers, as it affects physical growth, cognitive development, and future productivity. Nutritional management plays a crucial role in overcoming stunting, but parents often face challenges in providing adequate dietary intake due to limited knowledge, economic constraints, and lack of guidance. This community service program (PKM) aimed to strengthen parental involvement in managing toddler nutrition through structured home care nursing visits. The program was implemented with a participatory approach involving nurses, parents, and community health cadres. Home visits included nutritional assessments, individualized counseling, monitoring of toddler growth, and education on balanced diet preparation using locally available food resources. Nurses also provided practical demonstrations on menu planning and food processing to ensure nutrient adequacy. The evaluation showed improvements in parents’ knowledge and skills regarding child nutrition, with increased awareness of growth monitoring and the importance of dietary diversity. Furthermore, parents reported higher confidence in applying nutritional practices at home. These outcomes highlight that home care nursing visits can be an effective strategy to support parental roles in addressing stunting, particularly in low-resource settings. Strengthening family-centered care and promoting community engagement are essential to ensure the sustainability of nutritional improvements. This program demonstrates that empowering parents through direct home-based interventions can significantly contribute to reducing stunting prevalence and improving child health outcomes